Az egyesületi karitásztól az állami gondoskodásig: Szociális gyermekvédelem a századfordulón Budapesten - Kaszás, Marianne (Szociológiai Szemle, 2024)
This paper discusses social child care in Hungary around the turn of the century, at a time when it had outgrown the capacities of charity organizations and forced the state into active involvement in social child care. After a brief survey of the 19th century antecedents, the paper describes closed and open forms of social child care: educational institutes, financial aid and provisions made for abandoned children. The first government measures provided state funds for charity organizations and established laws decreeing the foundation of state orphanages. This development continued with the provision for foundlings by the authorities an culminated in the establishment of the first Hungarian Royal State Child Shelter in Budapest.